Relevance of TMPRSS2, CD163/CD206, and CD33 in clinical severity stratification of COVID-19 - Martínez-Diz, Silvia; Marín-Benesiu, Fernando; López-Torres, Ginesa; Santiago, Olivia; Díaz-Cuéllar, José F.; Martín-Esteban, Sara; Cortés-Valverde, Ana I.; Arenas-Rodríguez, Verónica; Cuenca-López, Sergio; Porras-Quesada, Patricia; Ruiz-Ruiz, Carmen; Abadía-Molina, Ana C.; et al. (Frontiers in Immunology, 2023)
Background: About 13.8 and 6.1% of COVID-19 patients require admission to hospital and sometimes in intensive care unit. There is any biomarker for anticipating who of those patients will develop an aggressive stage, so we could improve their quality of life and health system management. Our main aim is to include new markers for classifying COVID-19 patients. Methods: Two peripheral blood tubes from a total of 66 (n=34 mild and n=32 severe) samples (mean age 52 years old) were collected. A cytometry analysis using a 15-parameter included in Maxpar® Human Monocyte/Macrophage Phenotyping Panel Kit was performed. Cytometry by time-of-flight mass spectrometry (CyTOF) panel was performed in combination with a genetic analysis using TaqMan® probes of ACE2 (rs2285666), MX1 (rs469390) and TMPRSS2 (rs2070788) variants. GemStoneTM and OMIQ software were used for cytometry analysis. Results: Frequencies in the Transitional Monocytes (T-Mo) CD163+/CD206- population were decreased in mild group compared to severe one, while the T-Mo CD163-/CD206- were increased in mild group compared to severe group. In addition, in severe group we also found difference in CD11b expression in CD14dim monocytes, with decreased values in female group (p=0.0412) in severe patients clustering. When performing comparisons of mild versus severe we also found that CD45- (p=0.014; OR=0.286 95% CI (0.104-0.787)) and CD14dim/CD33+ (p=0.014; OR=0.286 95% CI (0.104-0.787)) monocytes are the best options as biomarkers for distinguishing between these group of patients. CD33 was also indicated as a good biomarker for stratifying patients by the analysis of GemStoneTM software. Among genetic markers, we found that G carriers of TMPRSS2 (rs2070788) have an increased risk (p=0.02; OR=3.37 95% CI (1.18-9.60)) for having severe COVID-19 contrasting to those with AA. This strength is reinforced when combing with CD45-, T-Mo CD163+/CD206-, and C14dim/CD33+. Conclusions: Here we report the interesting role of TMPRSS2, CD45-, CD163/CD206 and CD33 for COVID-19 aggressiveness. Which strength is reinforced for aggressiveness biomarkers when combining TMPRSS2 and CD45-, TMPRSS2 and CD163/CD206; TMPRSS2 and CD14dim/CD33+.